MBKM Policy Study: Independent Learning Curriculum Policy Analysis in the Indonesian Language Study Program Islamic University of Nusantara Bandung - Nurhasanah, Intan; Meliyanti, Meliyanti; Sumarni, Sri; Wasliman, Eva Diana; Wasliman, Iim (Civiliza Publishing, Indonesia., 2025)
The Merdeka Belajar Kampus Merdeka (MBKM) policy is expected to be able to answer the challenges of higher education in facing the demands of a dynamic world of work. This study aims to analyze the implementation of the MBKM policy in the Indonesian Language Education Study Program at Universitas Islam Nusantara Bandung. The approach used is descriptive qualitative with a policy study design, referring to the POAC managerial function (Planning, Organizing, Actuating, and Controlling). Data were collected through in-depth interviews, documentation studies, and participatory observations of lecturers, students, and study program managers. The results show that the MBKM policy has been implemented through various programs such as Teaching Campus and student entrepreneurship, but still faces obstacles such as cross-institutional coordination and limited technical understanding among students. Periodic evaluation and outcome-based curriculum adjustments are important strategies in addressing these challenges. This study concludes that the implementation of MBKM shows a positive direction, but still needs institutional strengthening, increased human resource competence, and integrated information system support. The findings are expected to be a reference for stakeholders in formulating higher education policies that are more adaptive and contextual.